Mapping RNAPII CTD Phosphorylation Reveals That the Identity and Modification of Seventh Heptad Residues Direct Tyr1 Phosphorylation - Burkholder, Nathaniel T; Sipe, Sarah N; Escobar, Edwin E; Venkatramani, Mukeshkumar; Irani, Seema; Yang, Wanjie; Wu, Haoyi; Matthews, Wendy M; Brodbelt, Jennifer S; Zhang, Yan (ACS chemical biology, 2019)
The C-terminal domain (CTD) of the largest subunit in eukaryotic RNA polymerase II has a repetitive heptad sequence of Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7 which is responsible for recruiting transcriptional regulatory factors. The seventh heptad residues in mammals are less conserved and subject to various post-translational modifications, but the consequences of such variations are not well understood. In this study, we use ultraviolet photodissociation mass spectrometry, kinetic assays, and structural analyses to dissect how different residues or modifications at the seventh heptad position alter Tyr1 phosphorylation. We found that negatively charged residues in this position promote phosphorylation of adjacent Tyr1 sites, whereas positively charged residues discriminate against it. Modifications that alter the charges on seventh heptad residues such as arginine citrullination negate such distinctions. Such specificity can be explained by conserved, positively charged pockets near the active sites of ABL1 and its homologues. Our results reveal a novel mechanism for variations or modifications in the seventh heptad position directing subsequent phosphorylation of other CTD sites, which can contribute to the formation of various modification combinations that likely impact transcriptional regulation.